Self-Healing Photocurable Epoxy/thiol-ene Systems Using an Aromatic Epoxy Resin - Ricardo Acosta Ortiz; Omar Acosta Berlanga; Aída Esmeralda García Valdez; Rafael Aguirre Flores; José Guadalupe Télles Padilla; María Guadalupe Méndez Padilla (Advances in Materials Science and Engineering)
A rapid and efficient method to obtain self-healing epoxy resins is discussed. This method is based on the use of a thiol-disulfide oligomer obtained by partial oxidation of a multifunctional thiol using a hypervalent iodine (III) compound as oxidant. The oligomer was characterized by Fourier transform infrared spectroscopy (FTIR), Raman and nuclear magnetic resonance spectroscopies, and gel permeation chromatography (GPC). The oligomer was a joint component of the thiol-ene system along with a tetra-allyl-functionalized curing agent. The kinetics of the photopolymerization of diglycidylether of bisphenol A (DGEBA) revealed that conversions of the epoxy groups as high as 80% were achieved in only 15 minutes by increasing the concentration of the thiol-ene system in the formulation. The disulfide bonds introduced in the copolymer using the thiol-disulfide oligomer allowed the repairing of the test specimens in as little as 10 minutes when the specimens were heated at 80°C or for 500 minutes at room temperature. The analysis of the mechanical properties using dynamic mechanical analysis (DMA) showed that the specimens displayed a healing efficiency up to 111% compared with the unhealed specimens, depending on the amount of polythioethers present in the copolymer.